Discovery and engineering of low work function perovskite materials. Issue 37 (24th August 2021) - Ma, Tianyu; Jacobs, Ryan; Booske, John; Morgan, Dane
Abstract : High throughput DFT simulations yield 7 low work function perovskites as promising cathode materials. Abstract : Materials with low work functions are critical for an array of applications requiring the facile removal or efficient transport of electrons through a device. Perovskite oxides are a promising class of materials for finding low work functions, and here we target applications in thermionic and field electron emission. Perovskites have highly malleable compositions which enable tunable work function values over a wide range, robust stability at high temperatures, and high electronic conductivities. In this work, we screened over 2900 perovskite oxides in search of stable, conductive, low-work-function materials using Density Functional Theory (DFT) methods. Our work provides insight into the materials chemistry governing the work function value of a perovskite, where materials with barely filled d bands possess the lowest work functions. Our screening has resulted in a total of seven promising compounds, such as BaMoO3 and SrNb0.75 Co0.25 O3 with work functions of 1.1 eV and 1.5 eV, respectively. These promising materials and others presented in this study may find use as low work function electron emitters in high power vacuum electronic and thermionic energy conversion devices. Moreover, the database of calculated work functions and materials chemistry trends governing the value of the work function may aid in the engineering of perovskite heterojunction devices.